Modelling the size and strength benefits of optimised step/scarf joints and repairs in composite structures - Pierce, Robert S.; Falzon, Brian G. (2019)
Adhesive bonding offers a better load transfer between adherends, for the assembly and repair of composite structures, compared with mechanical fastening methods. One drawback of adhesive bonded repairs is the considerable amount of material which must be removed, around the damaged region, to ensure adequate load transfer. Optimised geometries that account for the highly-orthotropic properties of individual composite plies are investigated, including a novel ‘fibre-oriented’ scarf approach that is inspired by an existing fibre-oriented step design. These methods aim to reduce the length of joint and repair bonding regions by at least 36%, compared with conventional step and scarf geometries of a similar strength. Size-reduction benefits are predicted using a MATLAB tool that is applicable for any composite laminate, and parametric analysis used to assess the effect of ply thickness, the number of plies, stacking sequence and taper angle. Cohesive Zone Models of joints and repairs with conventional and fibre-oriented designs are used to predict and compare the ultimate strength of each configuration. The existing fibre-oriented step design appears to show no benefit over a conventional step design. However, the novel fibre-oriented scarf approach results in a 33–40% reduction in the size of the bonding region compared to a conventional scarf design with similar strength. Analysis further indicates a 17–22% increase in ultimate strength for joints and repairs with the same bonding region size that employ the optimised fibre-oriented scarf design.